Knee Pain and a Prior Injury Are Associated With Increased Risk of a New Knee Injury: Data from the Osteoarthritis Initiative - Driban, Jeffrey B. (J Rheumatol, 2015)
OBJECTIVES: We explored if knee pain or a history of knee injury was associated with a knee injury in the following 12 months. METHODS: We conducted longitudinal knee-based analyses among knees in the Osteoarthritis Initiative. We included both knees of all participants who had at least one follow-up visit with complete data. Our first sets of exposures were knee pain (chronic knee symptoms and severity) at baseline, 12-month, 24-month, and 36-month visits. Another exposure was a history of injury, which we defined as a self-reported injury at any time prior to baseline, 12-month, 24-month, or 36-month visits. The outcome was self-reported knee injury during the past year at 12-month, 24-month, 36-month, and 48-month visits. We evaluated the association between ipsilateral and contralateral knee pain or history of injury and a new knee injury within 12 months of the exposure using generalized linear mixed model for repeated binary outcomes. RESULTS: A knee with reported chronic knee symptoms or ipsilateral or contralateral history of an injury was more likely to experience a new knee injury in the following 12 months than a knee without chronic knee symptoms (odds ratio [OR]=1.84, 95% confidence interval [CI]=1.57, 2.16) or prior injury (prior ipsilateral knee injury OR=1.81, 95% CI=1.56, 2.09; prior contralateral knee injury OR=1.43, 95% CI=1.23, 1.66). CONCLUSION: Knee pain and a history of injury are associated with new knee injuries. It may be beneficial for individuals with knee pain or a history of injury to participate in injury prevention programs.